Development of an integrated bio-rural energy scheme in Ghana - Nelson, Nii (2023)
Ghana like many sub-Saharan African countries faces significant social issues. Approximately 42% of Ghanaians live in rural areas where agriculture is a predominant livelihood activity. The total population below the poverty line is about 24.2%, with rural poverty almost 4 times as high as urban poverty. Among the many issues confronting Ghana, electricity access is a big concern for rural residents, who currently enjoy less than 30% access. This thesis aimed to develop and evaluate an integrated bio-rural energy scheme in Ghana using cocoa pod husks as feedstock. In order to achieve the aim of this study, biomass materials and their conversion technologies were reviewed. Following this, different varieties of cocoa pod husk materials were characterized using ultimate and proximate analyses. A numerical model for predicting the performance of cocoa pod husk gasification systems was also developed. Eventually, a dedicated rig was used to evaluate the performance of the cocoa pod husk-fed energy generation system. The study revealed that agricultural crop residue and livestock production have a theoretical energy potential of 728.43 PJ and 76.72 PJ, respectively. This is remarkable given that Ghana has a total installed generation capacity of 5134 MW. It was noted that cocoa pod husk has a higher heating value of 14.44-19.21 MJ/kg, which could be useful for power generation through gasification. The moisture content of cocoa pod husk was generally below 15% coupled with low levels of nitrogen and sulphur. There was a fairly good agreement between the results of the numerical model and those of the experiment after a few modifications. A peak carbon conversion efficiency of 75% was observed, although the efficiency of the gasifier system was generally low.